2015
DOI: 10.1016/j.jcmg.2014.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Plaque Characteristics by CT Angiography Identify Coronary Lesions That Cause Ischemia

Abstract: Objective We evaluated the association between atherosclerotic plaque characteristics (APCs) by coronary CT angiography (CT) and lesion ischemia by fractional flow reserve (FFR). Background FFR is the gold standard for determining lesion ischemia. While APCs by CT—including aggregate plaque volume % (%APV), positive remodeling (PR), low attenuation plaque (LAP) and spotty calcification (SC)—are associated with future coronary syndromes, their relationship to lesion ischemia is unclear. Methods 252 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
164
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 268 publications
(186 citation statements)
references
References 30 publications
15
164
5
2
Order By: Relevance
“…Using machine learning, they showed that a composite risk score integrating age, sex, and CT-based plaque characteristics (noncalcified plaque) was a better discriminator of vessels with impaired CFR than the stenosis severity alone. These results are consistent with a recent study by Park et al 11 demonstrating that total plaque volume and an aggregate model, including plaque volume, lesion length, and low attenuation plaques on coronary CTA, improved identification of stenosis associated with abnormal invasive fractional flow reserve.…”
Section: See Article By Dey Et Alsupporting
confidence: 92%
“…Using machine learning, they showed that a composite risk score integrating age, sex, and CT-based plaque characteristics (noncalcified plaque) was a better discriminator of vessels with impaired CFR than the stenosis severity alone. These results are consistent with a recent study by Park et al 11 demonstrating that total plaque volume and an aggregate model, including plaque volume, lesion length, and low attenuation plaques on coronary CTA, improved identification of stenosis associated with abnormal invasive fractional flow reserve.…”
Section: See Article By Dey Et Alsupporting
confidence: 92%
“…Future discrimination between these two completely different sources of coronary calcium might become a major breakthrough in CAC imaging, since spotty calcifications have been recognized as a marker of high risk plaques (81,82).…”
Section: Effect Of Statins On Cacmentioning
confidence: 99%
“…Recently this relation was also depicted using CCTA. In a study that included 252 stable patients undergoing both CCTA and ICA with FFR, Park et al were able to document an association between certain CCTA atherosclerotic plaque characteristics (APCs) and the presence of ischemia by invasive FFR (31). In their study, lesion length, positive remodelling (index ≥1.1), and the presence of low attenuation plaque (<30 HU) were independent predictors of ischemia by invasive FFR.…”
Section: Atherosclerotic Plaque Characteristics and Functional Informmentioning
confidence: 97%